Kegiatan Berbagi Kepedulian Melalui Donasi Pakaian Layak Pakai untuk Fakir Miskin di Desa Tropodo Waru Sidoarjo - She Fira Azka Arifin; Sufi Zakiya Khoirun Nisa; Muchammad Bachrul Alam (Jurnal Nusantara Berbakti, 2025)
The activity "Sharing Concern Through Donation of Suitable Clothing for the Poor in Tropodo Village, Waru, Sidoarjo" aims to help underprivileged communities in meeting their clothing needs. The background of this activity is the low economic conditions of the local community, so they prioritize food needs over clothing. This activity seeks to foster social solidarity by utilizing the culture of mutual cooperation in the community. The methods used include collecting suitable clothing from donors, sorting based on beneficiary categories, and distributing it directly to the poor who have been recorded. Through this activity, beneficiary communities can obtain more suitable clothing, increase their self-confidence, and reduce the negative impact of limited clothing on their welfare. The results of this activity show that donation of suitable clothing not only has an impact on the welfare of the recipients, but also increases social awareness in more affluent community groups. In addition, this activity strengthens relationships between residents and strengthens the values ​​of mutual cooperation in the community. Challenges in this activity include low community participation, logistical constraints, and varying quality of donations, which can be overcome with better education and coordination. With this activity, it is hoped that similar initiatives will emerge more widely, so that more people are encouraged to share and support each other.